PENDAMPINGAN MARKETING FUNDING DAN FINANCING PADA BANK PERKREDITAN RAKYAT SYARIAH “X” - Idah Zuhroh; Eris Tri Kurniawati; Muhammad Sri Wahyudi Suliswanto (Studi Kasus Inovasi Ekonomi, 2020)
Achievement of quantitative performance in Sharia Rural Banks (BPRS) "X" in the first semester of 2018 based on the first semester of 2018 financial statements which showed a trend compared to the financial statements of the second half of 2017. Required marketing and financing funds in this BPRS. This assistance activity can help increase the amount of financing in Murabahah at the BPRS Bumi Rinjani. Neither does the amount of savings or deposits.